Rural Researcher and Practitioner Responses to Misrecognition and Distributive Injustice - Guenther, John; Cuervo, Hernan (Australian and International Journal of Rural Education, 2024)
The articles in this issue can be viewed through the lens of theories of Recognition and Distributive Justice. These theories, when applied to rural education point to the marginalisation and devaluing of rural education, such that some kind remedy is required. The remedies for this are arguably the responsibility of systems that develop policies and provide funding for research and education. But we find that educators and researchers respond in their own way to the deficits and distributive injustices that are imposed on their roles in rural and remote communities. In the articles of this issue, we see researchers and practitioners investing their time, persisting and persevering despite apparent failure, engaging socially, and making space for the next generation of educators and researchers. The contexts in which these actions are taken vary, and so too do the expressions of these responses.